2013
DOI: 10.1021/ed300027f
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Alternative Conceptions of Preservice Teachers and High School Students Concerning Atomic Size

Abstract: The purpose of this study was to analyze and compare the alternative conceptions of high school students and preservice teachers on the concept of atomic size. The Atomic Size Diagnostic Instrument was developed; it is composed of eight, two-tier multiple-choice items. The results of the study showed that as a whole 56.2% of preservice teachers and 59.4% of high school students correctly answered six or more questions out of eight. New alternative conceptions about atomic size, which could be grouped under thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
(37 reference statements)
0
9
0
4
Order By: Relevance
“…Students were also ambiguous in titration calculations. This phenomena occurs in less meaningful learning as stated by Berg, Cross et al, and Pinarbasi [5,6,7]. Some researches recommend learning has to be plan with the more students active and partisipatory as well as accommodate the multiple representative especially in learning chemistry [3,4,8,9] .The important thing is student has to have a high motivation on learning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Students were also ambiguous in titration calculations. This phenomena occurs in less meaningful learning as stated by Berg, Cross et al, and Pinarbasi [5,6,7]. Some researches recommend learning has to be plan with the more students active and partisipatory as well as accommodate the multiple representative especially in learning chemistry [3,4,8,9] .The important thing is student has to have a high motivation on learning.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Yarroch (in Nakleh [5]) has carried out the research on misconceptions associated with chemical reaction.He reported that all students managed to equalize the equation, but most students could not draw molecular diagrams correctly to explain the similarities sub-microscopically. Regarding the size of atoms, Eymur et al [6] reported that students who are prospective teachers have misconceptions which are almost similarly experienced by high school students. Misconceptions are highly dependent on many factors, such as experience, creativity, perception, and textbooks.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, water molecules are reported to consist of hydrogen and oxygen molecules, or "molecule" and "atom" are used interchangeably. Furthermore, the atom is reported to have similar size to that of a molecule or even an ion when they have the same number of protons (Griffiths and Preston, 1992;Eymur et al, 2013); whereas, in other cases, the size of the atom is like a "point of a needle" or a "head of a pin"s (Harrison and Treagust, 1996;Cokelez, 2012). As for the lack of distinction between atom and cell, atoms are reported to be made of cells or to have properties of living organisms and biological functions (e.g., Cokelez, 2012;Harrison and Treagust, 1996).…”
Section: Students' Knowledge For the Atommentioning
confidence: 99%
“…Σε ηλικίες 17 έως 18 ετών, παρουσιάζεται η ιδέα ότι ʻτο άτομο είναι μεγαλύτερο από το μόριοʼ (Griffiths & Preston, 1992), όπως και η ιδέα (ηλικίες 15 έως 18 ετών και μελλοντικούς δασκάλους) ότι το άτομο με το αντίστοιχο ιόν του έχουν το ίδιο μέγεθος, επειδή έχουν τον ίδιο αριθμό πρωτονίων (Eymur, Çetin & Geban, 2013). Επιπλέον, οι Eymur, Çetin & Geban (2013) παρατηρούν, ότι το μέγεθος του ατόμου εξαρτάται από το ιοντικό φορτίο, γεγονός που φανερώνει δυσκολία στην αναγνώριση του μεγέθους των ατόμων κάθε στοιχείου και των αντίστοιχων ιόντων τους.…”
Section: νοητικά μοντέλα και αναπαραστάσεις η περίπτωση της αδυunclassified
“…Σε ηλικίες 17 έως 18 ετών, παρουσιάζεται η ιδέα ότι ʻτο άτομο είναι μεγαλύτερο από το μόριοʼ (Griffiths & Preston, 1992), όπως και η ιδέα (ηλικίες 15 έως 18 ετών και μελλοντικούς δασκάλους) ότι το άτομο με το αντίστοιχο ιόν του έχουν το ίδιο μέγεθος, επειδή έχουν τον ίδιο αριθμό πρωτονίων (Eymur, Çetin & Geban, 2013). Επιπλέον, οι Eymur, Çetin & Geban (2013) παρατηρούν, ότι το μέγεθος του ατόμου εξαρτάται από το ιοντικό φορτίο, γεγονός που φανερώνει δυσκολία στην αναγνώριση του μεγέθους των ατόμων κάθε στοιχείου και των αντίστοιχων ιόντων τους. Ακόμη και σε επίπεδο προπτυχιακών φοιτητών, παρουσιάζεται η δυσκολία στη διάκριση των μεγεθών, τόσο ανάμεσα στα άτομα όσο και ανάμεσα στα ιόντα (Nyachwaya et al, 2011) και στην αναγνώριση του μεγέθους της ατομικής ακτίνας, ανάμεσα σε διαφορετικά στοιχεία (Nicoll, 2001).…”
Section: νοητικά μοντέλα και αναπαραστάσεις η περίπτωση της αδυunclassified